Hepatic Glycerol Metabolism-Related Genes in Carnivorous Rainbow Trout (Oncorhynchus mykiss): Insights Into Molecular Characteristics, Ontogenesis, and Nutritional Regulation - Panserat, Stephane; Plagnes-Juan, Elisabeth; Gazzola, Elsa; Palma, Mariana; Magnoni, Leonardo J.; Marandel, Lucie; Viegas, Ivan (Frontiers in Physiology, 2020)
Glycerol metabolism in rainbow trout is poorly studied even though it is at the interface between lipid and glucose metabolism. Moreover, glycerol can be an important ingredient in new aquafeed formulation to decrease the catabolism of dietary amino acids. Thus, the present study had for objective to characterize for the first time the different genes coding for key enzymes and proteins involved in hepatic glycerol metabolism. From the trout genomes, all the paralogous genes coding for glycerol transport (aqp9b), glycerol kinase (gk2a and gk5), glycerol-3-phosphate phosphatase (pgp) and glycerol-3-phosphate dehydrogenase (gpd1a, gpd1b, gpd1c) were identified. The ontogenesis determined that the capacity to metabolize glycerol begins with the apparition of the liver during the development (stage 22) and are more expressed at the endogenous-exogenous feeding period (stage 35). The postprandial regulation of the expression of these genes in juvenile trout showed that the postprandial peak of expression is between 4h and 24h after the last meal for many of the genes demonstrating that the glycerol metabolism could be nutritionally regulated at a molecular level. However, surprisingly, no regulation of the glycerol metabolic mRNAs abundance by different levels of dietary glycerol (0%, 2.5%, 5%) have been detected, showing that the hepatic glycerol metabolism is poorly regulated at a molecular level by dietary glycerol in rainbow trout juveniles.